2018
DOI: 10.21831/reid.v3i2.17993
|View full text |Cite
|
Sign up to set email alerts
|

Quartet cards as the media of career exploration for lower-grade primary school students

Abstract: A career developed through the optimization of one's potentials will irrevocably play a role in the development of self-identity as well as the psychological well-being of the individual. When children are introduced and allowed to explore as many career options as possible during their developmental stage, they are more likely to have a fruitful career development in the future. The preceding study showed that the career interests and knowledge of lower-grade primary students fit the Holland Career Categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
1
0
1
Order By: Relevance
“…The previous findings also showed that the development of the quartet card media as a medium for student career exploration was declared feasible and very well used for students (Ayriza et al, 2017). These findings have differences in the variety of media developed by researchers and have similarities with the results in this study, which can be shown based on the scope of career information content presented in the media, which is developed based on Holland RIASEC career theory.…”
Section: Product Testing Phasesupporting
confidence: 75%
“…The previous findings also showed that the development of the quartet card media as a medium for student career exploration was declared feasible and very well used for students (Ayriza et al, 2017). These findings have differences in the variety of media developed by researchers and have similarities with the results in this study, which can be shown based on the scope of career information content presented in the media, which is developed based on Holland RIASEC career theory.…”
Section: Product Testing Phasesupporting
confidence: 75%
“…Self-exploration is more cognitive and can be Between Talents and Environment Impact during Pandemic COVID-19 done through self-reflection, self-optimization, and filling out instruments to help the career exploration process. Career development or career exploration through self-optimization plays an essential role in identity development and individual psychological well-being (Ayriza, Y., Setiawati, F. A., Triyanto, A., Gunawan, N. E., Anwar, M. K., & Budiarti, 2017). Career exploration precludes students from planning a career, focusing attention exclusively on the education major and type of work to be pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Pilihan karir yang tepat bagi siswa akan meningkatkan kepuasan dan kesuksesan mereka program studi dan pekerjaan di masa depan. karir yang dikembangkan melalui optimalisasi potensi seseorang akan dapat memainkan peran dalam pengembangan identitas diri serta kesejahteraan psikologis individu (Yulia Ayriza, 2017).…”
Section: Calculusunclassified